2017
DOI: 10.1097/brs.0000000000001714
|View full text |Cite
|
Sign up to set email alerts
|

Are They Complying? Physicians’ Knowledge, Attitudes, and Readiness to Change Regarding Low Back Pain Treatment Guideline Adherence

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Expertise in physiotherapy is achieved through formal education, as well as through years of clinical experience and on‐the‐job learning . Previous studies were inconclusive about whether seniority affects the attitudes of health care providers toward LBP: older and more experienced general practitioners exhibited more orthodox attitudes, but at the same time, experienced health care providers were shown to be less fearful of pain, which attests to more advanced psychosocial approaches. The latter finding in the current study appears to be the result of physiotherapists' abundant experience with LBP patients, and echoes the repeated evidence from nursing, according to which exposure to patients' pain results in desensitization to pain …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Expertise in physiotherapy is achieved through formal education, as well as through years of clinical experience and on‐the‐job learning . Previous studies were inconclusive about whether seniority affects the attitudes of health care providers toward LBP: older and more experienced general practitioners exhibited more orthodox attitudes, but at the same time, experienced health care providers were shown to be less fearful of pain, which attests to more advanced psychosocial approaches. The latter finding in the current study appears to be the result of physiotherapists' abundant experience with LBP patients, and echoes the repeated evidence from nursing, according to which exposure to patients' pain results in desensitization to pain …”
Section: Discussionmentioning
confidence: 97%
“…Psychometric evaluations have shown that the internal consistency of the instrument is satisfactory (Cronbach's α = 0.78/0.84, respectively) and the validity of the HC‐Pairs has been proven adequate, as a measure showing the statistical association between beliefs about pain and impairment. This instrument was translated into Hebrew as part of a recent study …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Practitioners' beliefs affect how they explain pain to the patient and what kind of care they choose [28,29]. Non-pharmacological treatment considering psychosocial factors is not given, as LBP guidelines and evidence suggest, if the attitudes and beliefs of the treating physician are biomedical [30]. It also matters which type of health care professional first sees the patient.…”
Section: Introductionmentioning
confidence: 99%